2007
DOI: 10.1371/journal.pone.0000685
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the UBIAD1 Gene, Encoding a Potential Prenyltransferase, Are Causal for Schnyder Crystalline Corneal Dystrophy

Abstract: Schnyder crystalline corneal dystrophy (SCCD, MIM 121800) is a rare autosomal dominant disease characterized by progressive opacification of the cornea resulting from the local accumulation of lipids, and associated in some cases with systemic dyslipidemia. Although previous studies of the genetics of SCCD have localized the defective gene to a 1.58 Mbp interval on chromosome 1p, exhaustive sequencing of positional candidate genes has thus far failed to reveal causal mutations. We have ascertained a large mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
1
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 43 publications
4
120
1
1
Order By: Relevance
“…The locations of the mutations identified in this as well as two prior publications [Orr et al, 2007;Weiss et al, 2007] revealed several clusters of mutations (Fig. 4A).…”
Section: Analysis Of the Potential Consequences Of The Mutationssupporting
confidence: 84%
See 4 more Smart Citations
“…The locations of the mutations identified in this as well as two prior publications [Orr et al, 2007;Weiss et al, 2007] revealed several clusters of mutations (Fig. 4A).…”
Section: Analysis Of the Potential Consequences Of The Mutationssupporting
confidence: 84%
“…Many of the mutations reported in this and prior studies [Orr et al, 2007;Weiss et al, 2007] were nonconservative amino acid substitutions. There were dramatic size and/or shape differences between the reference sequence and mutant amino acids in 7/8 mutations (N102S, D118G, L121F, S171P, T175I, G177R, G186R).…”
Section: Analysis Of the Potential Consequences Of The Mutationssupporting
confidence: 57%
See 3 more Smart Citations